RETRACTED: Di Paola et al. Combined Effects of Potassium Perchlorate and a Neonicotinoid on Zebrafish Larvae (Danio rerio). Toxics 2022, 10, 203 - Davide Di Paola; Fabiano Capparucci; Sabrina Natale; Rosalia Crupi; Salvatore Cuzzocrea; Nunziacarla Spanò; Enrico Gugliandolo; Alessio Filippo Peritore (Toxics)
The journal retracts the article, “Combined Effects of Potassium Perchlorate and a Neonicotinoid on Zebrafish Larvae (Danio rerio)” [...]